2014
DOI: 10.1186/1471-2458-14-774
|View full text |Cite
|
Sign up to set email alerts
|

Improving awareness of preconception health among adolescents: experience of a school-based intervention in Lebanon

Abstract: BackgroundMaternal behavior before and after conception affects maternal and child health. Limited awareness of adolescents in preconception health may be addressed through school education. The aim of this intervention is to assess preconception health awareness among adolescents in Lebanese high schools and to test the effectiveness of a one-time educational session in improving preconception knowledge.MethodsThe intervention consisted of a 30-minute educational session about good practices in preconception … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 19 publications
1
32
1
1
Order By: Relevance
“…In the present study nearly three-fifths of students were female, this observation in the same line with [6] who reported that the majority of students were female. Also [16] who apply an online study to identify undergraduates' knowledge and attitudes of preconception health care found that 77% of participant was female.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study nearly three-fifths of students were female, this observation in the same line with [6] who reported that the majority of students were female. Also [16] who apply an online study to identify undergraduates' knowledge and attitudes of preconception health care found that 77% of participant was female.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding marital status of students only 3.4% of them were married, this data disagreed with [6] who mentioned that more than one-fifth of the students were married. And nearly half (47.3%) of participants were married in [17], who performed their study in Hawassa, Ethiopia to assess knowledge of preconception health care among healthcare providers working in public health institutions.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations